3D-simulation of packing of aggregates with realistic morphology and size distribution, by using a real-time physics’ engine - Michot Roberto, Sonia Elisa (2022)
Granular materials are present in almost every field of science, from the pharmacy industry to civil engineering. Their study has been the objective of numerous research to understand better how the particle properties influence final material quality. Particularly in the engineering field, a more in-depth study of stone-based materials is important, as the effect of the grain's size and shape and their arrangement and orientation influence their workability, durability, and mechanical properties. Nevertheless, the current models of granular materials have been unable to deal with some drawbacks, as the generation of realistic randomised 3D particles. This is due to the lack of mathematical models to represent the irregular shape of aggregates, being those oversimplified by primitive or convex polyhedrons; or the computational cost involved in computing the interaction between the numerous particles of a granular assemblage, because to most of the current numerical models require prohibitive consumer-grade hardware when entering complex shape; especially when those have concavities. To overcome those barriers, a virtual physical model for aggregate's assemblies at the mesoscale level has been developed using an impulse-based discrete element numerical method, commonly used for video game and animation industries, which is implemented in a physics engine. Based on a simple analysis of aggregates through Image Analyse software, the model can generate many particles with realistic, complex shapes (including concavities) and size distribution quickly and automatically. Another important contribution is the creation of a new simulations approach of aggregate's packing that can be used to simulate stone-based materials with specific applications such as asphalt's aggregate structures, ballast or any other similar granular system, providing a starting point for future research. Although the model is still at its very beginning, the results obtained from the simulations are quite close to the experimental ones, which indicates its ability to be used as a design tool for granular materials. However, there are still some limitations to overcome, as hardware and software capabilities, which will be overcome with further technological advances. KEYWORDS: